Drug utilization pattern in an intensive care unit of a teaching hospital in South India - B., Suraj; ., Srikanth; C., Somashekara S.; B., Sandeep; ., Tanuja (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Polypharmacy and inappropriate usage of antibiotics are common in an Intensive Care Unit (ICU) which may increase morbidity, mortality, antimicrobial resistance and treatment cost. Hence, drug utilization research is crucial for measuring drug consumption using DDD/100 bed-days formula proposed by the WHO that would possibly be useful while formulating a comprehensive antibiotic policy for the institution and guide for future inter-hospital or institutional comparisons. Therefore, in this study, we proposed to evaluate the drug utilization patterns in the ICU. Methods: A prospective observational study was conducted for 3 months from June 2018 to August 2018, and the data were obtained from the ICU of a tertiary care hospital. The demographic data, disease data, the utilization of different classes of drugs (WHO-ATC classification) as well as individual drugs were recorded. Results:One hundred and twelve patient’s data were evaluated. About 90% patients were prescribed with antiulcer medications during their ICU stay followed by antibiotics in more than 89% patients. Azithromycin, levofloxacin, metronidazole, ofloxacin, ceftriaxone and amoxicillin/clavulanic acid were maximally utilized antibiotics with 24, 16.43, 14.27, 13.89, 12.22 and 10.97 DDD/100 bed-days respectively. Conclusions: Antiulcer medications were most commonly prescribed followed by antibiotics during ICU stay. Average numbers of drugs prescribed per patients were high. Regular prescription audit and modification of antibiotic policy is required to curtail the polypharmacy and inappropriate use of antibiotics. Background: Polypharmacy and inappropriate usage of antibiotics are common in an Intensive Care Unit (ICU) which may increase morbidity, mortality, antimicrobial resistance and treatment cost. Hence, drug utilization research is crucial for measuring drug consumption using DDD/100 bed-days formula proposed by the WHO that would possibly be useful while formulating a comprehensive antibiotic policy for the institution and guide for future inter-hospital or institutional comparisons. Therefore, in this study, we proposed to evaluate the drug utilization patterns in the ICU. Methods: A prospective observational study was conducted for 3 months from June 2018 to August 2018, and the data were obtained from the ICU of a tertiary care hospital. The demographic data, disease data, the utilization of different classes of drugs (WHO-ATC classification) as well as individual drugs were recorded. Results:One hundred and twelve patient’s data were evaluated. About 90% patients were prescribed with antiulcer medications during their ICU stay followed by antibiotics in more than 89% patients. Azithromycin, levofloxacin, metronidazole, ofloxacin, ceftriaxone and amoxicillin/clavulanic acid were maximally utilized antibiotics with 24, 16.43, 14.27, 13.89, 12.22 and 10.97 DDD/100 bed-days respectively. Conclusions: Antiulcer medications were most commonly prescribed followed by antibiotics during ICU stay. Average numbers of drugs prescribed per patients were high. Regular prescription audit and modification of antibiotic policy is required to curtail the polypharmacy and inappropriate use of antibiotics. Keywords: Antibiotics, Daily defined doses, Drug utilization, Intensive care unit